Histological Study of Small Intestine in the Adult Guinea Fowl - Mahdi, Rawaa Taha (American Journal of Biology and Natural Sciences, 2025)
Due to the importance of small intestine and its important role of the digestion and absorption process, as well as the economic importance of guinea fowl (Numida meleagris). The current investigate was conducted to study the segments of small intestine (Duodenum, Jejunum, and Ilium) histologically in guinea fowl. Samples were taken from the small intestine of (10) healthy adult males of guinea fowl after slaughtering them and separating the small intestinal from its appendages. All samples were subjected to histological techniques. In the current study, three kinds of stains were used when conducting the histological study, which are, Heamatoxylin and Eosin stain, the Masson trichrome stain and Periodic Acid-Schiff stain. From inner to outer, the wall of small intestine was lined with four tunicae: Mucosa, Submucosa, Muscularis, and Serosa. The small intestine's mucosa was flung into villi, which are protrusion. Columnar and goblet cells lined the various sections of the small intestine, which had varying small intestinal villi in terms of structure and arrangement. The intensity of Goblet cells were increment from Duodenum to Ileum. The Lamina propria, which comprised cells and connective tissue fibers, made up the majority of the villus' core. It was nearly impossible to distinguish the thin, poorly developed submucosa from the muscularis externa underneath it, unless when there were big blood vessels present. There are no Brunner glands visible in the intestinal submucosa. Tunica muscularis appeared as longitudinal smooth muscle bundles on the outside and inner circular muscle bundles on the inside. Collagen fibers made up the majority of tunica serosa with blood vessels and adipose tissue.